Biocombustíveis no contexto da política de transição energética do Brasil: contribuições, limites e possibilidades diante da necessidade de justiça climática no capitaloceno - Assis, Nery dos Santos de (2024)
The climate emergency has imposed a new agenda on international relations, bringing to regulation the need to reconcile different fields of knowledge, such as law, energy studies, economic, political and social issues, with multiple interests, agendas and demands that need to be modulated, not for the sake of immediate interests, but for future generations and human existence. Based on the concepts of climate justice and energy transition, this paper seeks to analyze the role of biofuels within Brazil's energy transition strategy. It was presented how the capitalocene is responsible for an unprecedented crisis that threatens the existence of life on the planet. It was emphasized that technologies need to be more than sustainable, because it is no longer enough for them to be renewable, they also need to be clean, in order to be able to break the catastrophic future that lies ahead. In this context, Brazilian biofuels such as ethanol and biodiesel stand out in comparison with the electric motor matrix in the reorganization of the light vehicle and cargo fleet, in the definition of the transition policy. Through a literature review, the use of indirect comparative research using the Life Cycle Analysis method (ISO 14040 to 14044 and ABNT-ISO 14040), documentary research in normative documents, a comparison was made between different forms of motorization, from internal combustion engines powered by fossil and renewable fuels, 100% electric engines and hybrid engines of different generations, in an attempt to identify the relationship between the choice of motorization of the fleet and the factors that influenced the political decision making for certain energies to the detriment of others. The work thus demonstrates that in the current context and the global perspectives for structuring a new model of society that is not based on carbon and exploitation are indispensable conditions for the transition, not only of energy, but of the relationship between man and nature. The perspectives of alternatives ranging from the global green new deal to the construction of a new society, including the theory of degrowth, are presented as proposed solutions to the problem currently facing us - the climate crisis. The way out of the change in degrowth economics on these issues (economic transition or societal transition) and Brazilian regulation strategies in this global framework of legal- political regulation. The hypothesis that biomass biofuels are clean and renewable energies with the potential to contribute to actions compatible with the global GHG emission reduction targets for 2050 was presented and verified. The paper presents an inventory of the methodologies used to calculate the carbon footprint of each energy matrix, in order to guide policies that could lead to a situation of zero or negative GHG emissions. Brazil's energy transition policy follows a global green new deal model and relies on technological solutions as an alternative to the climate crisis, although there are contradictions between the proposed model and political and economic practice, there is no social change (focused on needs rather than growth) underway, and that the Brazilian option is no different from that of developed countries, that national biofuels do not occupy the position they should occupy in the transition, either as a technology or as a change in society.